COPYRIGHT PROTECTION IN TELECOMMUNICATIONS NETWORKS: THE EXAMPLE OF BLOCKCHAIN TECHNOLOGY - Abdumumin Yuldashov; Vosid Usmonov (Journal Park Publishing, 2022)
The article deals with the issues of ensuring the protection of copyright objects when using them in telecommunication networks. In particular, the role of blocking means in this direction, methods and technical requirements for protection, as well as the processes of regulation of legal relations in this direction are described. In addition, the article describes the world experience in this direction, the role of the “Internet contracts” of the World Intellectual Property Organization, technical means of protecting copyright on the Internet, as well as the norms and practice of the legislation of Uzbekistan. It is substantiated that the use of blockchain technology in the protection of copyright objects is an effective tool, and issues related to its application are widely discussed. After all, it is important to ensure not only copyright in telecommunication networks and the Internet, but also the development of this area, the widespread use of these networks in the provision of public services, the security of the information they contain. At the same time, it was noted that the most important aspect of this system (blockchain) is characterized by the fact that digital information in it is integral and unshakable, that is, the reliability of the system plays an important role in increasing the efficiency of monetary transactions and information exchange between individuals and corporations.
Keywords: copyright; blockchain; telecommunication network